Is the voiced-voiceless phonemic boundary influenced by an intensity level of the presentation - Slawinski, E.B.; MacNeil, J.F. (Canadian Acoustics, 1994)
The duration of voice onset time (VOT) is a dominant and decisive phonetic correlate of the phonemic (voiced) contrast for stop consonants in a word-initial position. Thus, the difference in the duration of VOT in naturally produced plosive consonants in the initial position of words serves to distinguish voiced and voiceless tokens spoken by native talkers of eleven languages (Lisker & Abramson, 1964). However, it was also found that beside the VOT other acoustical cues contribute to the phonemic boundary expressed by the VOT. For example, a longer VOT is required to judge a phoneme as voiceless when first formant (F1) transition is longer or F1 frequency onset is lower (Summerfield & Haggard, 1977). Moreover, an analysis of speech production data demonstrated that voiced and voiceless stop-consonants vary also in the peak intensity and in the duration of the burst of frication noise. The frication noise is of a longer duration and of a higher intensity at the release of a voiceless plosive (Klatt, 1975). Thus, the perceptual categorization of bilabial stop-consonants in word-initial position, while mostly relying on a difference in the VOT, should also depend on an acoustical cue such as loudness of the noise burst. Therefore, the present study examined the influence of the intensity level (sound pressure level) of a stimulus presentation on the voiced/voiceless phonemic boundary between bilabial stop consonants in the initial position of words